2021
DOI: 10.1016/j.jtumed.2021.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Does spasticity affect the postural stability and quality of life of children with cerebral palsy?

Abstract: Objectives Cerebral palsy is a unique physical disability that primarily affects children's gross motor functions and postural control. Cerebral palsy has a direct impact on children's daily activities and quality of life. This study aims to determine the relationship between spasticity, motor function, postural stability, and the quality life of children with cerebral palsy. Methods Forty-five children (age range 4–6 years) diagnosed with spasticity from cerebral palsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Postural control during walking can be indicative of underlying health problems. The body’s postural control significantly impacts the quality of life [ 29 , 30 ]. Using wearable devices to measure posture can be inconvenient for participants [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Postural control during walking can be indicative of underlying health problems. The body’s postural control significantly impacts the quality of life [ 29 , 30 ]. Using wearable devices to measure posture can be inconvenient for participants [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has mainly focused on the relation between spasticity or reflex hyper-excitability and muscle activity during walking (Nielsen et al, 2020). Only two prior studies specifically investigated reactive standing balance and found no relation between joint hyper-resistance as measured by MAS and CoM movement (Ali, 2021) or the ability to withstand perturbations without stepping (de Niet et al, 2013). In contrast to prior studies, we did not only assess general resistance or the neural response to muscle stretch but also muscle co-activation, as a sign of reduced reciprocal inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Two prior studies investigated the relationship between joint hyper-resistance and reactive standing balance. These studies found no relationship between the Modified Ashworth Scale (MAS) and respectively CoM movement during standing in children with CP (Ali, 2021) and the ability to withstand perturbations without stepping in children with hereditary spastic paraparesis (de Niet et al, 2013). To our knowledge, the relationship between reduced reciprocal inhibition in response to isolated joint rotations and increased muscle co-activation during functional movements has not been studied.…”
Section: Introductionmentioning
confidence: 96%
“…Children with spastic diplegic CP often exhibit a greater degree of impairment in the lower extremities compared to other regions of the body. This typically manifests as challenges in maintaining an upright posture of the trunk due to the inherent instability caused by a high center of mass and a limited base of support (3) . It was demonstrated that children with spastic diplegic CP had worse trunk control and maintaining balance than typically developing children.…”
Section: Introductionmentioning
confidence: 99%